FROM LINEAR TO CIRCULAR ECONOMY: THE ROLE OF REGIONAL AWARENESS AND INITIATIVES - Delcart, Louis (International Journal of Research -GRANTHAALAYAH, 2021)
Although many OECD countries are working on it, the economy is only slowly developing from linear to circular. However, many economists are convinced that this is the only viable path if we want to prevent a climate catastrophe by 2050 and thereby leave a habitable and developable world for the next generations. Numerous articles in the press point out that many companies are only at the beginning of a gigantic effort to make their production CO2 neutral but also sustainable and that a lot of innovation will be needed before that happens. So, what are the reasons why the transition towards a circular economy is so difficult to make? The European Academy of the Regions, that advocates the regionalisation of a number of economic and socio-cultural sectors, closely follows the development of the circular economy. Since the beginning of May 2021, it has therefore set-up a blog in which newspaper articles are translated from various countries to English with examples of successful circular economy initiatives or of critical studies: earaercircular.tumblr.com. To date, the organisation made a statistical study on the 100 selected articles[1] published between 3/5/2021 and 3/9/2021 that will give the reader an idea of the themes that are most frequently discussed and of the remedies that are created. The articles come from newspapers and magazines from Belgium (Dutch and French), the Netherlands, Germany, Spain and the US and to a lesser extent from Switzerland, Canada and France. The results of this research are an overview of the topics covered, of indications of how initiatives are created, who is the influencer as well as an overview of the articles that have received more than 100 clicks on social media. It has been striking that many of the initiatives described by the press have arisen from companies whose top management is aware of the bend that urgently needs to be made and who also see commercial opportunities to start early. There are also a number of cooperative initiatives, that still succeed in creating successful initiatives from a small-scale approach. A second important player in this conversion is the academic world, especially faculties or even entire universities that have been conducting research into new materials or new applications for a long time. The traditional third player are the authorities, but very often regional governments or large cities. The conclusion remarks show that circular economy can only be successful if companies see a profit model in it, or are forced to change their course by public opinion because of negative perception and that we are not yet there.